2002
DOI: 10.1037/0021-9010.87.5.894
|View full text |Cite
|
Sign up to set email alerts
|

Four heads are better than one: Combining face composites yields improvements in face likeness.

Abstract: Abstract.Four different participants constructed face composites, using "PRO-Fit", of familiar and unfamiliar targets, with reference images present or from memory. The "mean" of all four composites, created by morphing (4-Morph) was rated as a better likeness than individual composites on average, and was as good as the best individual likeness. When participants attempted to identify targets from line-ups, 4-Morphs again performed as well as the best individual composite. In a second experiment participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
113
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(128 citation statements)
references
References 15 publications
15
113
0
Order By: Relevance
“…Brace, Pike, Kemp, 2000;Bruce, Ness, Hancock, Newman & Rarity, 2002;Davies, Van der Willik & Morrison, 2000;Frowd, Bruce, Ness et al, 2007;Frowd, Skelton, Butt, Hassan, & Fields, 2011). When the retention interval is up to a few hours in duration, for example, composites are named with a mean accuracy of around 10 to 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Brace, Pike, Kemp, 2000;Bruce, Ness, Hancock, Newman & Rarity, 2002;Davies, Van der Willik & Morrison, 2000;Frowd, Bruce, Ness et al, 2007;Frowd, Skelton, Butt, Hassan, & Fields, 2011). When the retention interval is up to a few hours in duration, for example, composites are named with a mean accuracy of around 10 to 20%.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found that E-FIT and PRO-fit produce composites that are correctly named about 20% of the time when participant-witnesses attempt construction either immediately or a few hours after seeing a target face (Brace et al 2000, Bruce et al 2002, Davies et al 2000, Frowd et al 2004, 2005b, 2007a, 2007b. Unfortunately, when participant-witnesses are required to wait two days prior to construction, a situation typical of real witnesses, composite naming normally falls to a few percent correct at best (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is a sensible finding because age range would contribute to variability for the reasons stated earlier in this section -more time allows for more natural and lifestyle changes in facial appearance. Importantly, morphs produced more similar depictions than average ratings collapsed across all artists, likely because morphs minimized idiosyncratic features depicted by individual artists as in composite sketches [3]. This indirectly indicates that inter-artist reliability for images of the same targets negatively affects target similarity.…”
Section: Natural and Lifestyle Factors Over Timementioning
confidence: 98%
“…Comments on an early draft of this paper were that, given that our stimuli rendered only Caucasian faces, non-Caucasians may perceive 3 Interpretation of effect sizes are taken from Cohen [5], such that small η them in a different way than Caucasians (e.g., featurally vs. holistically) and this could affect the interpretability of our results. The number of non-Caucasians (N = 13) was too small to directly compare responses by race, but we could estimate the effect by re-analyzing the data without these participants and observing whether the effects and patterns change.…”
Section: Cross-race Concernsmentioning
confidence: 99%